(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
The main objective of the following article is to analyze the constitution of argentine Sports Medicine and, in particular, to focus on the sports medical proposal prepared by Gofredo Grasso and his particular view of women and sports in the decades of ‘20 and ‘30. We are interested in investigating the ways in which Grasso’s proposal conceptualized the female body and sexuality in a context of accelerated changes and deep social, cultural, economic, political, legal and sexual transformations. At the same time, the senses that condensed the sports medical proposal of Dr. Gofredo Grasso while constructing Lilian Harrison as one of the first argentine record woman athletes, will be analyzed.